Perbandingan Model Pembelajaran Kooperatif Tipe Teams Games Tournament dengan Model Pembelajaran Kooperatif Tipe Think Pair Share Terhadap Hasil Belajar - Sindiani, Sindiani; Suherti, Heti; Afriza, Edi Fitriana (LPPM Institut Pendidikan Nusantara Global, 2024)
This research is motivated by the problems that occur, at SMAN 5 Tasikmalaya, namely the low student learning outcomes. The method used is a quasi-experimental method with The Nonequivalent Control Group Design. The results showed that there were differences in the improvement of student learning outcomes seen from the average value of the posttest of the experimental class 1 which was 87.56, the average value of the posttest of the experimental class 2 which was 81.14, and the average value of the posttest of the control class which was 73.60. These results prove that the comparison in experimental class 1 can improve student learning outcomes better than the learning process in experimental class 2 and control class with international trade material in class XI IPS SMAN 5 Tasikmalaya.